World Heritage sites of Britain - Smith, Roland 1944- (Basingstoke AA, 2010)
Here the author takes you on a tour of the 25 UNESCO World Heritage Sites that can be found in Britain. Accompanying his informative text are fabulous photographs bringing to life these places of interest.
Includes index.
"A guide to all of Britain's world-class places of interest" -- Cover.
Keywords: Historic sites -- Great Britain -- Guidebooks; Great Britain -- Guidebooks